PEMBERDAYAAN SISWA SMK MELALUI TECHNOPRENEUR KAPSUL NANOKALSIUM DARI CANGKANG TELUR AYAM - Sunardi, Sunardi; Mahayana, Argoto; Hafizah, Dila Auli; Sumardiyono, Sumardiyono; Prasasti, Anin; Alfiana, Ina; Iswandi, Iswandi; Putri, Hana Maylinda; Kuncahyo, Ilham; Sugiyarmasto, Sugiyarmasto; Hidayati, Nur; Soebiyanto, Soebiyanto; Gunawan, Lucia Sincu (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
The partner in this Community Service Program is SMK TUNAS NUSANTARA, Industrial Chemistry Department in Jaten, Karanganyar. Students in this department do not yet have knowledge about waste-based technopreneur. One of the opportunities that can be taken is to produce nanocalcium herbs from chicken eggshells. Partners face several obstacles, namely: 1) Lack of knowledge of Industrial Chemistry SMK students about calcium; 2) Limited knowledge and skills in making nanocalcium herbal capsules; and 3) Lack of knowledge and skills related to food safety, packaging, and marketing. To overcome these problems, the Community Service program is carried out through: 1) Making herbal nanocalcium from eggshell; 2) Training on making nanocalcium herbal capsules; 3) Marketing management training. As a result, the partners succeeded in producing nanocalcium herbal capsules that are beneficial for bone health and now have the provision to become technopreneurs.